Evolved but Not Fixed: A Life History Account of Gender Roles and Gender Inequality - Zhu, Nan; Chang, Lei (Frontiers in Psychology, 2019)
The rift between evolutionary psychology and the biosocial model of gender relations impedes a fuller understanding of gender roles and gender inequality. In a novel evolutionary account that complements both existing theories, we highlight life history strategies as intermediate mechanism linking distal environmental forces to variations in gender relations. Specifically, traditional versus modernized gender roles are seen as shaped by present-oriented versus future-oriented reproductive strategies, which are sensitive to uncontrollable morbidity-mortality risks. Gender inequality stem from a combination of present-oriented reproductive strategies adapted to high-risk environments and dominance hierarchies resulting from societal competition (i.e., the probability of obtaining resources desired by others through personal efforts). By contrast, gender egalitarian values develop as people increasingly enact future-oriented reproductive strategies in a competitive but orderly and controllable environment, which is conducive to prestige hierarchies. The current account provides novel interpretations of phenomena ranging from sex differences in mate preference, sociosexuality, and sexism to cross-cultural variability in marital systems and cultural practices. All of these serve to support the view that gender relations are evolved, changeable, and influenced by the interaction between ecological and social environments in ways predicted by the life history mechanism.